2019
DOI: 10.1111/1756-185x.13511
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness and safety of rituximab in the treatment of rheumatoid arthritis: A single‐center experience in Taiwan

Abstract: Aim To assess the real‐world effectiveness and safety of rituximab (RTX) at 24 months in patients with established rheumatoid arthritis (RA) and to identify predictors of low disease activity/remission and a good European League Against Rheumatism (EULAR) response. Methods Seventy RTX‐treated RA patients were enrolled. Predictors for low disease activity/remission and a good EULAR response at 24 months were identified by multivariate analyses. Results At 24 months, the mean Disease Activity Score of 28 joints—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…RTX is a chimeric type I monoclonal anti CD20 antibody, consisting of a human Fc portion and a murine variable region which serve as CD20 binding site (119). RTX was first licensed for use in B-cell malignancies (120), however, it is currently used in several autoimmune disorders, and has been recently licensed as first-line treatment in pemphigus (121124). RTX target, CD20, is a transmembrane receptor, that is expressed across various developmental stages of the B-cell, from the pre-B cell to the mature; while, early precursor pro-B cells and antibody-producing plasma cells do not express it (125).…”
Section: Treatmentmentioning
confidence: 99%
“…RTX is a chimeric type I monoclonal anti CD20 antibody, consisting of a human Fc portion and a murine variable region which serve as CD20 binding site (119). RTX was first licensed for use in B-cell malignancies (120), however, it is currently used in several autoimmune disorders, and has been recently licensed as first-line treatment in pemphigus (121124). RTX target, CD20, is a transmembrane receptor, that is expressed across various developmental stages of the B-cell, from the pre-B cell to the mature; while, early precursor pro-B cells and antibody-producing plasma cells do not express it (125).…”
Section: Treatmentmentioning
confidence: 99%
“…A total of 16,934 patients were included in the 21 studies. Remission criteria was defined as disease activity score (DAS28) of less than or equal to 2.6 [ 11 23 , 26 , 28 , 30 ]. Other studies used the simplified disease activity index (SDAI) score of less than or equal to 3.3 to assess for remission [ 24 , 25 , 27 , 29 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 , respectively. We performed meta-analyses for six sociodemographic-related factors including age older than 55 year old (fifteen studies [ 11 , 12 , 14 , 15 , 18 , 20 23 , 25 , 28 31 ]), female gender (sixteen studies [ 11 , 14 17 , 19 25 , 27 , 30 , 31 ]), obesity defined as BMI ≥ 30 kg/m 2 (four studies [ 16 , 21 , 27 , 31 ]), smoking status defined as current or ex-smoker (seven studies [ 11 , 14 16 , 18 , 21 ]), poor baseline functional status defined as Health Assessment Questionnaire (HAQ) of more than two (nine studies [ 11 , 14 , 16 , 20 , 21 , 24 , 25 , 27 ]), and presence of comorbidities (three studies [ 11 , 15 ]). Our analysis showed that old age (OR 0.98 (0.97, 0.99), P < 0.00001), female gender (OR 0.66 (0.56, 0.77), P < 0.00001), BMI > 30 (OR 0.95 (0.91, 0.99), P 0.02), smoking history (OR 0.86 (0.75, 0.99), P 0.04), and baseline HAQ > 2 (OR 0.62 (0.48, 1.27), P < 0.00001) are significantly associated with low rate of remission.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations